The preventive role of marital counseling programs targeting early shared trauma in promoting the resilience of family relationships in Palestine (Journal of the College of Basic Education, 2026)
The Protective Impact of Marriage Counseling Programs Targeting Early Shared Trauma on Enhancing Family Resilience in the Northern GovernoratesObjective: This study aimed to understand the protective impact of marriage counseling programs targeting early shared trauma on enhancing family resilience in the Northern Governorates of Palestine.Methodology: A qualitative research approach was employed. To achieve the study's objectives, data was collected through interviews with a sample of ten randomly selected couples.Results: The findings revealed that marriage counseling programs addressing early shared psychological trauma have a significant protective effect in enhancing family resilience in the Northern Governorates. These programs provided a safe environment for processing such trauma (90% agreement), strengthened communication and listening skills (100% agreement), and fostered empathy and mutual understanding (90% agreement). This significantly contributed to improving relationship quality (70% agreement) and equipping couples with practical tools to navigate future challenges.Conclusion: The study recommends expanding the scope of these preventive programs, developing specialized counseling curricula for shared psychological trauma, reinforcing communication and empathy skills as foundational to counseling, training specialized counselors, providing post-counseling support and follow-up programs, and launching community awareness campaigns to highlight the importance of marriage counseling as a positive tool for enhancing family stability and resilience.